تخريج الفروع المتعلقة بالصلاة في كتاب "الأم" على الأصول المتعلقة بالكتاب والسنة في كتاب "الرسالة" : دراسة تحليلية تطبيقية - Abdullah Muhammad Sofyan (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
Copying and mimicking becomes more common among students nowadays. They receive provisions without take a deep look to its origins and identifying methods. Other than considering eliciting the provisions for the current scourges. Although there are great efforts for (Al-Ijtihad). As Imam Al-Shafi'i left us with the first fundamental “Al-Risala” and his jurisprudence original writings “Al-Umm”, in which he presented: - his scientific method to study scripts and eliciting provisions, and the correlation between ascendants and descendants applicably. Therefore, this research's aim is to study the approach of Imam Al-Shafi'i in implementation and rooting. Because through subdivision the origin of the methods of the al-Mujtahid (that acknowledge both al-Fiqh and its origins) and study his methodology on how to elicit provisions and track the origins that he applied and relied on. Which help building the jurisprudence capability with which the student can find the hadith origins according to today's issues and knowing the provisions relating to Al Imam's origins Sharia. The researcher adopted the inductive approach to track the origins of the book and Al-Sunna that been mentioned in both books “Al-Risala” and “Al-Umm”. Then tracked Al Shafi'i follower's sayings. And the disagreements between the three (mathhab) without going through their arguments. Also, he applied the analytical approach to analyze Al Shafi'i scripts whether ascendants or descendants. And disagreements between Al-Imam and his follower if there is any. And that through showing the origins approach on descendants over ascendants. And Al-Shafi'i and the origins related to the research. Then finding the hadith origins of prayers according to Quran or Sunna, then finding the origins of them both with correlations. And Al-Shafi'i approach in finding origins. The conclusion of the research is that the Shafi'i school of thought is in between. In the people of the hadith and the people of opinion, and that several sayings between the old and the new may affect al-fiqh, and work on the new sayings, and his companions may favor the old saying, as they followed his methods after his death. In his approach there was the origin of al-Hadith finding, means there are fixed origins of al-Hadith and the mujtahdeen including.